For those who don't know part 2 (omega)

Algebra Level 5

( 9 7 ω 9 ω 2 7 5 3 ω 2 5 ω 3 ) 8 = ? \left ( \frac { 9-7 \omega}{9\omega ^2 - 7} - \frac {5-3\omega^2}{5\omega - 3} \right )^8 = \ ?

If you like this problem try to solve this

Details and Assumption

ω \omega denotes the cube root unity ( 1 \ne 1 )


The answer is 81.0000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Discussions for this problem are now closed

Sujoy Roy
Dec 25, 2014

X = ( 9 7 ω 9 ω 2 7 5 3 ω 2 5 ω 3 ) 8 X=(\frac{9-7\omega}{9\omega^2-7}-\frac{5-3\omega^2}{5\omega-3})^8

= ( ω 9 7 ω 9 7 ω ω 2 5 3 ω 2 5 3 ω 2 ) 8 =(\omega\frac{9-7\omega}{9-7\omega}-\omega^2\frac{5-3\omega^2}{5-3\omega^2})^8

= ( ω ω 2 ) 8 =(\omega-\omega^2)^8

= [ ( ω ω 2 ) 2 ] 4 =[(\omega-\omega^2)^2]^4

= [ ω 2 + ω 2 ] 4 =[\omega^2+\omega-2]^4

= ( 3 ) 4 = 81 =(-3)^4=\boxed{81}

i also apply this steps...

Trishit Chandra - 6 years, 5 months ago

Nice solution , stucked on 3rd line, +1

U Z - 6 years, 5 months ago

Note :the solution is the first two lines only the other paragraphs are only for more understanding.

Because ω \omega is one of the cubic roots of 1 1 ω 3 = 1 \therefore { \omega }^{ 3 }=1

X = ( 9 7 ω 9 ω 2 7 5 3 ω 2 5 ω 3 ) 8 = ( 9 ω 3 7 ω 9 ω 2 7 5 ω 3 3 ω 2 5 ω 3 ) 8 = ( ω ( 9 ω 2 7 ) 9 ω 2 7 ω 2 ( 5 ω 3 ) 5 ω 3 ) 8 = ( ω ω 2 ) 8 = ( ± 3 i ) 8 = 81 i 8 = 81 \boxed { X={ (\frac { 9-7\omega }{ 9{ \omega }^{ 2 }-7 } -\frac { 5-3{ \omega }^{ 2 } }{ 5\omega -3 } ) }^{ 8 }={ (\frac { 9{ \omega }^{ 3 }-7\omega }{ 9{ \omega }^{ 2 }-7 } -\frac { 5{ \omega }^{ 3 }-3{ \omega }^{ 2 } }{ 5\omega -3 } ) }^{ 8 }={ (\frac { \omega (9{ \omega }^{ 2 }-7) }{ 9{ \omega }^{ 2 }-7 } -\frac { { \omega }^{ 2 }(5\omega -3) }{ 5\omega -3 } ) }^{ 8 }={ (\omega -{ \omega }^{ 2 }) }^{ 8 }={ (\pm \sqrt { 3 } i) }^{ 8 }=81{ i }^{ 8 }=\boxed { 81 } }

  • For those who don't understand why ( ω ω 2 ) = ± 3 i { (\omega -{ \omega }^{ 2 }) }=\pm \sqrt { 3 } i ω = 1 ± 3 i 2 t h e n ω 2 = ( 1 ± 3 i 2 ) 2 = 1 3 i 2 \quad \quad \omega \quad =\quad \frac { -1\pm \sqrt { 3 } i }{ 2 } \quad then\quad { \omega }^{ 2 }={ (\frac { -1\pm \sqrt { 3 } i }{ 2 } ) }^{ 2 }=\frac { -1\mp \sqrt { 3 } i }{ 2 } , so ( ω ω 2 ) { (\omega -{ \omega }^{ 2 }) } could be ( ω ω 2 ) = ( 1 + 3 i 2 ) ( 1 3 i 2 ) = 3 i { (\omega -{ \omega }^{ 2 }) }=(\frac { -1+\sqrt { 3 } i }{ 2 } )-(\frac { -1-\sqrt { 3 } i }{ 2 } )=\sqrt { 3 } i or could be ( ω ω 2 ) = ( 1 3 i 2 ) ( 1 + 3 i 2 ) = 3 i { (\omega -{ \omega }^{ 2 }) }=(\frac { -1-\sqrt { 3 } i }{ 2 } )-(\frac { -1+\sqrt { 3 } i }{ 2 } )=-\sqrt { 3 } i

( ω ω 2 ) = ± 3 i \therefore { (\omega -{ \omega }^{ 2 }) }=\pm \sqrt { 3 } i

  • For those who don't understand why ω = 1 ± 3 i 2 \omega =\frac { -1\pm \sqrt { 3 } i }{ 2 } and ω 2 = 1 3 i 2 { \omega }^{ 2 }=\frac { -1\mp \sqrt { 3 } i }{ 2 }

( copied from Kalpok Ethbrw solution )

X 3 = 1 { X }^{ 3 }=1 or ( x 1 ) ( x 2 + x + 1 ) = 0 (x-1)(x^2+x+1)=0

Either x = 1 x=1 or, x 2 + x + 1 = 0 x^2+x+1=0 Then x = 1 ± 1 2 4.1.1 2.1 x = \frac { - 1 \pm \sqrt{ -1^2 - 4.1.1 } } { 2.1} or, x = 1 ± 3 2 x = \frac { - 1 \pm \sqrt{ -3 } } { 2} or, one root of x is 1 + 3 . i 2 . \frac{-1+\sqrt{3}.i} {2}. This is called ω \omega if we take ω 2 {\omega }^{ 2 } We will discover it is another root of the equation. The root is 1 3 . i 2 . \frac{-1-\sqrt{3}.i} {2}.

Note : we can also take ω = 1 3 i 2 \omega =\frac { -1-\sqrt { 3 } i }{ 2 } then ω 2 = 1 + 3 i 2 { \omega }^{ 2 }=\frac { -1+\sqrt { 3 } i }{ 2 }

ω = 1 ± 3 i 2 \therefore\omega =\frac { -1\pm \sqrt { 3 } i }{ 2 } and ω 2 = 1 3 i 2 { \omega }^{ 2 }=\frac { -1\mp \sqrt { 3 } i }{ 2 }

Chew-Seong Cheong
Dec 28, 2014

Since ω \omega and ω 2 \omega^2 are complex cubic roots of 1 1 :

ω 3 = 1 \quad \Rightarrow \omega^3 = 1 and ω 2 + ω + 1 = 0 \omega^2 + \omega + 1 = 0

Therefore,

X = ( 9 7 ω 9 ω 2 7 5 3 ω 2 5 ω 3 ) 8 = ( 9 ω 2 7 ω 3 ω 2 ( 9 ω 2 7 ) 5 ω 3 ω 3 ω ( 5 ω 3 ) ) 8 \quad X = \left( \dfrac {9-7\omega}{9\omega^2-7} - \dfrac {5-3\omega^2}{5\omega - 3} \right)^8 = \left( \dfrac {9\omega^2-7\omega^3}{\omega^2(9\omega^2-7)} - \dfrac {5\omega-3\omega^3}{\omega(5\omega - 3)} \right)^8

= ( 9 ω 2 7 ω 2 ( 9 ω 2 7 ) 5 ω 3 ω ( 5 ω 3 ) ) 8 = ( 1 ω 2 1 ω ) 8 \quad \quad = \left( \dfrac {9\omega^2-7}{\omega^2(9\omega^2-7)} - \dfrac {5\omega-3}{\omega(5\omega - 3)} \right)^8 = \left( \dfrac {1}{\omega^2} - \dfrac {1}{\omega} \right)^8

= ( ω 3 ω 2 ω 3 ω ) 8 = ( ω ω 2 ) 8 = ( ( ω ω 2 ) 2 ) 4 \quad \quad = \left( \dfrac {\omega^3}{\omega^2} - \dfrac {\omega^3}{\omega} \right)^8 = \left( \omega - \omega^2 \right)^8 = \left( (\omega - \omega^2)^2 \right)^4

= ( ω 2 2 ω 3 + ω 4 ) 4 = ( ω 2 2 + ω ) 4 = ( ω 2 + ω + 1 3 ) 4 \quad \quad = \left( \omega^2 - 2\omega^3+\omega^4 \right)^4 = \left( \omega^2 - 2 + \omega \right)^4 = \left( \omega^2 + \omega + 1 - 3 \right)^4

= ( 0 3 ) 4 = 81 \quad \quad = \left( 0 - 3 \right)^4 = \boxed {81}

( 9 7 ω 9 ω 2 7 5 3 ω 2 5 ω 3 ) 8 M u l t i p l y i n g a n d d i v i d i n g ω i n t h e n u m e r a t o r a n d d e n o m i n a t o r o f b o t h t h e t e r m s . = ( ( ω ) 9 7 ω ( ω ) 9 ω 2 7 ( ω ) ( ω ) 5 3 ω 2 ( ω ) 5 ω 3 × 1 ω ) 8 = ( 9 7 ω 9 ω 3 7 ω ( ω ) 5 ω 3 ω 3 5 ω 3 × 1 ω ) 8 B u t ω 3 = 1 , S o = ( 9 7 ω 9 7 ω ( ω ) 5 ω 3 5 ω 3 × 1 ω ) 8 C a n c e l l i n g l i k e t e r m s , = ( ω 1 ω ) 8 P u t t i n g ω a s 1 + 3 2 , = ( 1 + 3 2 1 1 + 3 2 ) 8 R a t i o n a l i z i n g t h e s e c o n d t e r m , w e g e t 1 ω = ω 2 = ( 1 + 3 2 1 3 2 ) 8 = ( 1 2 + 3 2 + 1 2 + 3 2 ) 8 = ( 3 ) 8 = 81 \quad \quad \quad \quad \quad \quad \quad \quad { (\frac { 9-7\omega }{ 9{ \omega }^{ 2 }-7 } -\frac { 5-3{ \omega }^{ 2 } }{ 5\omega -3 } ) }^{ 8 }\\ Multiplying\quad and\quad dividing\quad \omega \quad in\quad the\quad numerator\\ and\quad denominator\quad of\quad both\quad the\quad terms.\\ \quad =\quad { ((\omega )\frac { 9-7\omega }{ (\omega )9{ \omega }^{ 2 }-7(\omega ) } -\frac { (\omega )5-3{ \omega }^{ 2 }(\omega ) }{ 5\omega -3 } \times \frac { 1 }{ \omega } ) }^{ 8 }\\ \quad \\ =\quad { (\frac { 9-7\omega }{ 9{ \omega }^{ 3 }-7\omega } (\omega )-\frac { 5\omega -3{ \omega }^{ 3 } }{ 5\omega -3 } \times \frac { 1 }{ \omega } ) }^{ 8 }\\ But\quad { \omega }^{ 3 }=1,\\ So\quad =\quad { (\frac { 9-7\omega }{ 9-7\omega } (\omega )-\frac { 5\omega -3 }{ 5\omega -3 } \times \frac { 1 }{ \omega } ) }^{ 8 }\\ \\ Cancelling\quad like\quad terms,\\ \quad =\quad { (\omega -\frac { 1 }{ \omega } ) }^{ 8 }\\ Putting\quad \omega \quad as\quad \frac { -1+\sqrt { 3 } }{ 2 } ,\\ \quad =\quad { (\frac { -1+\sqrt { 3 } }{ 2 } -\frac { 1 }{ \frac { -1+\sqrt { 3 } }{ 2 } } ) }^{ 8 }\\ Rationalizing\quad the\quad second\quad term,\quad we\quad get\quad \frac { 1 }{ \omega } \quad =\quad { \omega }^{ 2 }\\ \quad =\quad { (\frac { -1+\sqrt { 3 } }{ 2 } -\frac { -1-\sqrt { 3 } }{ 2 } ) }^{ 8 }\\ \quad =\quad { (-\frac { 1 }{ 2 } +\frac { \sqrt { 3 } }{ 2 } +\frac { 1 }{ 2 } +\frac { \sqrt { 3 } }{ 2 } ) }^{ 8 }\\ \quad =\quad { (\sqrt { 3 } })^{ 8 }\quad =\quad 81

Cheers!:)

Sanjeet Raria
Dec 27, 2014

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...